Indeks Massa Tubuh dan Kejadian Jerawat pada Siswa-Siswi SMA Muhammadiyah 1 Pontianak - Safira Sukma Dewinda; Ambar Rialita; Mahyarudin Mahyarudin (Politeknik Kesehatan Kemenkes Mamuju, 2020)
Acne vulgaris affects about 85% of adolescents and can last into adulthood. One of the factors that influence the pathogenesis of acne vulgaris is androgens. Androgens have an essential role in stimulating sebum production, which has a significant role in the pathogenesis of acne vulgaris. Obesity is often accompanied by peripheral hyperandrogenism. Obesity can affect the sebaceous glands and sebum production, which is the major factor in the relationship between acne vulgaris and obesity. The purpose of this study was to determine the relationship between Body Mass Index and the incidence of acne vulgaris. This study used an observational analytic research design with a cross-sectional approach. The study was conducted at Muhammadiyah 1 Pontianak Senior High School. Samples were taken using simple random sampling. The independent variable in this study was the body mass index while the dependent variable in this study was acne vulgaris. Sampling was conducted by simple random sampling. We used a logistic regression test for data analysis. The results showed that 61% of students experienced acne vulgaris, and 20.7% of students were obese. The statistical test result showed there was a significant positive correlation relationship between BMI and the incidence of acne vulgaris with a value of p <0.05 and OR 2.807. This study concluded that there was a significant positive correlation between BMI and the incidence of acne vulgaris. The incidence of acne vulgaris increased by 2,807 times as the increase of BMI among students in Muhammadiyah 1 Pontianak Senior High School.